Spermiogram changes in patients with mumps orchitis - Tatjana Roganović; Vladimir Krivokuća (Биомедицинска истраживања, 2014)
Introduction: . Mumps is a systemic viral infection characterized by swelling of salivary glands, especially the parotid glands. Gonads, meninges, pancreas and other organs may also be affected. The aim of this study was to analyze clinical and ultrasound characteristics of mumps orchitis, as well as to analyze spermiogram in patients treated for mumps orchitis in Infectious Diseases Clinic during mumps epidemic from October 2011 to December 2012. Methods: . The study included 90 patients with mumps orchitis. We analyzed clinical and laboratory parameters, ultrasound testicular changes (one month after the infection) and spermiogram (six months after the infection). Results: . The average age of patients was 21.4 years. In every third patient orchitis occurred in the course of parotitis, and for the rest of the patients orchitis occurred after parotitis. Orchitis was unilateral in 84% of the patients. Ultrasound testicular changes were present in 74.4% of the patients, and in 68.9% of them changes were unilateral. The average CRP value was 80.7 mg/L and it was significantly (p=0.014) higher in patients with bilateral orchitis. The average number of spermatozoids was higher in patients with unilateral orchitis than in patients with bilateral orchitis and the difference was statistically significant (p=0.011). Three patients with bilateral orchitis had azoospermia. Semen volume was below reference limit in 58.8% of patients with unilateral orchitis, while the results for patients with bilateral orchitis were insufficient. There was no statistically significant difference (p=0.100) in sperm motility between patients with unilateral and bilateral orchitis. Conclusion: . Patients with severe clinical features (bilateral orchitis) had more distinct changes in semen analysis. It is recommended to enable cryopreservation of sperm immediately after the diagnosis of orchitis, especially bilateral, as a possible solution in case of infertility.
Keywords: mumps; orchitis; spermiogram